Tumour necrosis factor α −308G→A polymorphism is not associated with response to TNFα blockers in Caucasian patients with rheumatoid arthritis: systematic review and meta-analysis. Issue 6 (4th December 2009) - Pavy, Stephan; Toonen, Erik J M; Miceli-Richard, Corinne; Barrera, Pilar; van Riel, Piet L C M; Criswell, Lindsey A; Mariette, Xavier; Coenen, Marieke J H
Abstract : Background: There is a need for biomarkers that can predict anti-tumour necrosis factor (anti-TNF) treatment outcome in patients with rheumatoid arthritis (RA). Several studies have suggested that the rare A allele of the tumour necrosis factor α (TNFA) −308G→A polymorphism could be associated with a poorer response to anti-TNF therapy. Nevertheless, these results remain controversial. Objective: To determine by a meta-analysis whether the TNFA −308G→A polymorphism is associated with response to anti-TNF treatment in patients with RA. Methods: A bibliographic search identified studies in which the TNFA −308G→A gene polymorphism was investigated in Caucasian patients with RA treated with anti-TNF agents. Complementary data were requested when the 28-joint count Disease Activity Score (DAS28) was not used as the primary outcome measure. Odds ratios (ORs) for response based on DAS28 and standardised mean difference (SMD) for mean improvement of DAS28 were calculated to assess the potential association between TNFA −308 genotypes and response to anti-TNF agents. Results: The bibliographic search yielded 12 studies that met the inclusion criteria, which were supplemented with the data from a large Dutch cohort (n=426). The OR based on the 12 studies including 1721 patients was 1.24 (95% CI 0.98 to 1.56) and the SMD based on 11 studies including 2579 patients was −0.18 (95% CI −0.36 to 0.1). Subgroup analysis based on the two classes of anti-TNF agents did not demonstrate any association between TNFA −308 genotypes and anti-TNF treatment outcome. Conclusion: According to this meta-analysis, the TNFA −308 polymorphism is not a predictor of the clinical response to anti-TNF treatment in RA.